Investment decisions in a high-inflation environment - Marco Schito; Luka Klimavičiūtė; Rozália Pál (European Investment Bank (EIB), 2024)
Does increasing inflation affect firms' investment decisions? This article employs the European Investment Bank Investment Survey (EIBIS) dataset to explore the association between the increased inflation that the EU countries have experienced since 2021, and firms' investment decisions. We find evidence that very high rates of inflation (over 20%) are associated with higher probabilities of investment, likely driven by measures to improve energy efficiency (particularly for SMEs) and a desire to avoid the devaluation of cash reserves (for large firms). We further find a positive association between SMEs' ability to pass costs onto consumers (the so-called pass-through rate) and investment decision, suggesting a higher degree of reliance on the generation of continuous revenues for investment purposes compared with large firms. Inflation's by-products (increased interest rates, difficulties in accessing external financing, increasing uncertainty) are found to be important negative factors in investment decisions. (146 words)
Keywords: D22; D25; E31; E43; 330; EIBIS; inflation; investment; cost pass-through rate; financial tightening; SMEs